Nano-SMSI on Bimetallic FePt Clusters - Waleska-Wellnhofer, Natalie; Freiberger, Marie; Hemauer, Felix; Schwaab, Valentin; Papp, Christian (Journal of Physical Chemistry C, 2023)
Nano-strong metal-support interaction is observed in this work for bimetallic FePt nanoclusters on graphene/Rh(111). FePt clusters were prepared by successively depositing 1.27 ML Fe and 0.14 ML Pt on the graphene/Rh(111) substrate. Oxidation of Fe was achieved by CO dissociation, while CO was simultaneously used as a probe molecule to gather information about the clusters’ structure. After UHV annealing to 550 K, encapsulation of Pt with an Fe oxide layer and a strong decrease of the chemisorption capacity of the clusters was found. Further increase of the temperature to 900 K leads to the decomposition of the Fe oxide layer and the intercalation of Fe. Besides, the formation of an FePt alloy was observed at elevated temperature.
CRIS-Team Scopus Importer:2023-11-03